MORPHOMETRIC ANALYSIS OF THE FORAMEN MAGNUM DIMENSIONS AND ITS RELATION TO GENDER - Rehman, Pooja Gangrade; Yadav, Rajeev; Deshpande , Gunjan (Journal of Forensic Medicine and Toxicology, 2011)
Introduction: The sex determination of human skeletons is important in forensic and anthropological research. It can be carried out through qualitative or quantitative analysis of morphological parameters of dimorphism. The base of the cranium is very complex in itself making the study of the diameters of foramen magnum even more important from a descriptive or topographic point of view. Aim: The aim of this study was to evaluate the effectiveness of the linear morphometric parameters and the area of foramen magnum for gender determination in human skulls. Material and Method: A total of 100 skulls (50 male and 50 female) were analyzed for their sagittal and transverse diameters, with the help of sliding vernier caliper (0.01) mm. The total area and the linear morphometric data thus obtained were analyzed and put to statistical analysis using students ‘t’ test. Results: The transverse diameter and the area of the foramen magnum were found to be significantly higher (p < 0.05), in the male skulls (29.03 ± 2.524 mm & 813 ± 114.7 mm2 respectively) than in the female skulls (27.87 ± 3.16 mm & 752.0 ± 158.2 mm2 respectively). Conclusion: The transverse diameter and the area of the foramen magnum were found to be significantly higher in male than female skulls and thus can be used in conjunction with other anthropological techniques for gender determination of unknown skulls.